2010
DOI: 10.3141/2144-13
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Benefits: Application of Customer Loyalty Modeling in Public Transportation Context

Abstract: This paper provides a demonstration of potential applications of customer loyalty modeling in the public transportation industry. Customer loyalty modeling investigates the cumulative effects of influencing factors on customers’ tendencies to choose one service or product over another for a particular need. Industries, such as airlines and telecommunications, model customer loyalty extensively to better understand and improve customer retention. A review of the literature returned only one direct application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 27 publications
(20 reference statements)
4
71
0
1
Order By: Relevance
“…To increase loyalty among disloyal riders, transit agencies should communicate the benefits of using transit to these groups and focus on maintaining a safe, clean, and convenient system (Figler et al 2011;Lai and Chen 2011;Minser and Webb 2010). However, transit agencies should also invest in better understanding the specific needs and desires of this group, as it is not clearly understood why these users are strongly disloyal.…”
Section: Captive-by-choice Users (~13%)mentioning
confidence: 99%
“…To increase loyalty among disloyal riders, transit agencies should communicate the benefits of using transit to these groups and focus on maintaining a safe, clean, and convenient system (Figler et al 2011;Lai and Chen 2011;Minser and Webb 2010). However, transit agencies should also invest in better understanding the specific needs and desires of this group, as it is not clearly understood why these users are strongly disloyal.…”
Section: Captive-by-choice Users (~13%)mentioning
confidence: 99%
“…The typical characteristics of loyal passengers were defined as repeat patronage, willingness of recommending to others, and high price tolerance. However, Minser and Webb [19] defined the public transit loyalty based on the likeliness of continuous service usage and willingness to recommend. They analyzed the empirical data collected from the Chicago Transit Authority by using a SEM and found that the quality of service, perceived value of service, satisfaction, and corporate image were the key factors affecting passengers' loyalty.…”
Section: Introductionmentioning
confidence: 99%
“…We developed integrated items -related to previously shown antecedents of patient loyalty -with social media. After exploring and confirming factor structure of developed constructs, we tested the conceptual model (as shown in Figure 1) within a Structural Equation Modelling (SEM) framework, which is a common methodology, in order to investigate the concept of customer loyalty (Chou and Kim, 2009;Matzler et al, 2007;Minser and Webb, 2010).…”
Section: The Current Studymentioning
confidence: 99%